NalO(4)/LiBr-mediated diastereoselective dihydroxylation of olefins: a catalytic approach to the prevost-woodward reaction - Emmanuvel, Lourdusamy; Shaikh, T. M. A.; Sudalai, A. (Organic Letters, 2005)
LlBr catalyzes efficiently the dihydroxylation of alkenes to afford syn and anti diols with excellent diastereoselectivity depending upon the use of NaIO4 (30 mol %) or Phl(OAc)(2) (1 equiv), respectively, as the oxidants. The oxidation of non-benzylic halides has been achieved for the first time to afford the corresponding diols in excellent yields.

NaIO4/KI/NaCl: a new reagent system for iodination of activated aromatics through in situ generation of iodine monochloride - Emmanuvel, Lourdusamy; Shukla, Ravi Kant; Sudalai, Arumugam; Gurunath, Suryavanshi; Sivaram, Swaminathan (Tetrahedron Letters, 2006)
A new reagent system consisting of NaIO4/KI/NaCl in aq AcOH has been found to be effective in iodinating a variety of activated aromatic substrates via in situ-generated iodine monochloride, to furnish iodoaromatics in excellent yields. This iodination procedure has been applied successfully for a cost-effective synthesis of 3,3'-diaminobenzidine, a key intermediate for preparing proton conducting membranes for fuel cell applications, with high yield and a purity of 99.7%. (c) 2006 Elsevier Ltd. All rights reserved.

NaIO4-mediated selective oxidation of alkylarenes and benzylic bromides/alcohols to carbonyl derivatives using water as solvent - Ali Shaikh, Tanveer Mahammad; Emmanuvel, Lourdusamy; Sudalai, Arumugam (Journal of Organic Chemistry, 2006)
A new transition-metal-free, sodium metaperiodate (NaIO4)-mediated direct oxidation of methylarenes and benzylic bromides to the corresponding aromatic carboxylic acids is described. Under the same reaction conditions, benzylic alcohols are selectively oxidized to afford the corresponding aldehydes in good yields without undergoing overoxidation. Unprecedentedly, oxidation of benzyl bromide, toluene, or benzyl alcohol with NaIO4 underwent nuclear bromination followed by oxidation to give 4-bromobenzoic acid in 60-79% yields.

NaIO4/LiBr-Mediated direct conversion of benzylic alcohols and aromatic aldehydes to aromatic esters - Shaikh, Tanveer Mohammad Ali; Emmanuvel, Lourdusamy; Sudalai, Arumugam (Synthetic Communications, 2007)
Aromatic aldehydes or benzylic alcohols are directly converted to the corresponding aromatic esters in high yields on treatment with methanol or ethanol mediated by sodium metaperiodate (NaIO4)/LiBr in an acidic medium.
Keywords: aromatic ester; benazaldehyde; Benzyl alcohol; Lithium bromide; Sodium metaperiodate